PENGARUH KESADARAN MEREK, ASOSIASI MEREK DAN KESAN KUALITAS TERHADAP KEPUTUSAN MEMBELI PONSEL MEREK NOKIA (STUDI PADA MAHASISWA UNIVERSITAS TRUNOJOYO) - Darul Islam; A. Yahya Suryawinata; Mohammad Arief (Neo-Bis, 2010)
Succesfully firm to create a strong brand will be impact to consumer’s buying decision reinforcement. From the empirical study, Lake (2010) argue that strong brand will be push a consumer’s to increase a product purchase. That indicator will use to define a strong brand can be identified from the brand equity. Conceptually, there are four component which forming brand equity , that is Brand Awareness, Brand Association, Brand Image dan Perceived (Aaker, 1991). 　　The aims of the research is to test the influence of brand awareness, brand association and perceived quality to purchase decision on Nokia Handphone. The subject of research conducted to Trunjoyo University student which used a Nokia Product Brand. Total sample that used to this studi is 100 respondent, determined by using non probability purpossive sampling. Primary data were collected and analyzed by using the technics of Multiple Regression Analysis. The result of this research indicates that brand awareness variable (X1) brand assosiation variabel (X2) and  perceived quality variabel (X3) simultaneously has significant affect to purchase decision. From the partial test, each variables show has a significant effect to purchase decision. From the analisys also found that the dominant variable which influence to purchase decision is brand awareness.